The circadian clock gene PER2 enhances chemotherapeutic efficacy in nasopharyngeal carcinoma when combined with a targeted nanosystem. Issue 24 (27th May 2020) - Hou, Li; Li, Hailiang; Wang, Haiyan; Ma, Dede; Liu, Jing; Ma, Liqiong; Wang, Zhihua; Yang, Zhihua; Wang, Faxuan; Xia, Hechun
Abstract : A schematic representation of PER2 overexpression combined with FURH-PFH-NPs that enhances synergistic chemotherapeutic efficacy in NPC. Abstract : Treatment failure occurs in more than 40% of advanced nasopharyngeal carcinoma (NPC) patients including local recurrence and distant metastasis due to chemoradioresistance. Circadian clock genes were identified as regulating cancer progression and chemoradiosensitivity in a time-dependent manner. A novel nanosystem can ensure the accumulation and controllable release of chemotherapeutic agents at the tumour site at a set time. In this study, we investigated the expression of circadian clock genes and identified that period circadian regulator 2 ( PER2 ) as a tumour suppressor plays a key role in NPC progression. A label-free proteomic approach showed that PER2 overexpression can inhibit the ERK/MAPK pathway. The chemotherapeutic effect of PER2 overexpression was assessed in NPC together with the nanosystem comprising folic acid (FA), upconverting nanoparticles covalently coupled with Rose Bengal (UCNPs-RB), 10-hydroxycamptothecin (HCPT) and lipid-perfluorohexane (PFH) (FURH-PFH-NPs). PER2 overexpression combined with the targeted and controlled release of nanoagents elevated chemotherapeutic efficacy in NPC, which has potential application value for the chronotherapy of tumours.